Plasma Nuclear and Mitochondrial DNA Levels, and Markers of Inflammation, Shock, and Organ Damage in Patients with Septic Shock. Issue 6 (June 2016) - Timmermans, Kim; Kox, Matthijs; Scheffer, Gert Jan; Pickkers, Peter
ABSTRACT: Background: Plasma levels of the danger-associated molecular patterns (DAMPs) nuclear DNA (nDNA) and mitochondrial DNA (mtDNA) have been shown to be related to sepsis mortality. However, the intermediate factors and/or mechanisms contributing to this relation are largely unknown. Our aim was to determine whether plasma levels of nDNA and mtDNA are related to the markers of inflammation, severity of shock, and organ damage in septic shock patients. Moreover, we investigated the relationship between plasma levels of nDNA/mtDNA and inflammatory cytokines during experimental human endotoxemia, a model of systemic inflammation in humans in vivo mimicking some of the hallmarks of early sepsis. Methods: Blood was sampled from the onset of septic shock until day 28 in 121 septic shock patients and from 1 h before endotoxin administration until 8 h afterward in 12 healthy volunteers. Plasma concentrations of five cytokines and circulating levels of nDNA and mtDNA were measured, and correlations with shock-related parameters and markers of organ damage were investigated. Results: In septic shock patients plasma cytokine concentrations, as well as nDNA and mtDNA levels, were increased at the onset of septic shock and remained elevated. During the first 5 days of septic shock, nDNA levels consistently correlated with plasma cytokine concentrations as well as with the shock-related parameter norepinephrine infusion rate and markers of organ damage (total bilirubin and creatinine). Experimental human endotoxemia also resulted in increased levels of plasma nDNA and mtDNA, but to a lesser extent than in septic shock patients. Furthermore, nDNA levels correlated with pro-inflammatory cytokines during endotoxemia. Conclusions: Our findings indicate a relationship between plasma nDNA levels and the inflammatory response. Furthermore, nDNA levels are associated with markers of shock and organ damage in septic shock patients. Nevertheless, the correlations found are relatively weak and it remains to be determined whether nDNA is merely a marker or directly involved in the pathophysiology of septic shock.